125. The Clinical Impact of 16S rRNA Bacterial Sequencing in Infective Endocarditis - El-Dalati, Sami (Open Forum Infect Dis, 2019)
BACKGROUND: Cases of possible and/or culture-negative endocarditis continue to be a diagnostic challenge. Performing bacterial 16S ribosomal RNA polymerase chain reaction (rRNA PCR) sequencing on cardiac valves now allows providers to make microbiologic diagnoses that were previously unobtainable (sensitivity 66–80.5%). However, few publications address how the PCR results impact clinical management in endocarditis patients. METHODS: Between July 1, 2014 and December 31, 2018, the results of all 16S rRNA PCR tests collected from cardiac valves at the University of Michigan were reviewed. Samples were sent to the University of Washington for sequencing. Each chart was then reviewed by two independent ID physicians to determine whether patients’ medical plans were impacted by the PCR results. RESULTS: 41 patients were identified with associated 16S rRNA PCR testing from cardiac valves. 16 cases met Duke Criteria for definite endocarditis, 22 for possible and 3 were rejected endocarditis. Overall, 18 (43.9%) samples were positive. Of these, 10 patients had concordant positive blood cultures. In 8 patients a previously unsuspected organism was identified. Twenty-four out of 41 patients were considered to have culture-negative endocarditis with October 24 (41.7%) who had positive PCR results. Twenty-two patients were noted to have operative findings consistent with infection with 16 (72.7%) having corresponding positive PCR results. 4/41 (9.8%) patients had their management plans changed based solely on the PCR findings. In 23/41 (56.1%) cases the PCR result was never referenced by any medical provider in the electronic medical record. There were 7 (17.1%) cases where patients received 6 weeks of antibiotics despite presenting with possible culture-negative endocarditis, noninfectious operative findings and negative valve PCRs which were not reviewed. CONCLUSION: 16S rRNA PCR sequencing is a useful tool for obtaining a microbiologic diagnosis in cases of possible or culture-negative endocarditis. The test has significant potential to impact individual patient care and in a subset of cases may be used to de-escalate antibiotic therapy. However, testing delays and cumbersome resulting methods impede bacterial sequencing from reaching its full potential as a diagnostic modality. [Image: see text] DISCLOSURES: All authors: No reported disclosures.